Harmonic Diversity and Determining Factors of Radial Forces in External Rotor Permanent Magnet Synchronous Motors with Concentrated Windings - Krotsch, Jens; Piepenbreier, Bernhard (ICEM, 2010)
In external rotor permanent magnet synchronous motors, also the higher frequency harmonics of the radial forces generate considerable resonant vibrations and acoustic noise. Therefore, diversity of spatial and especially frequency harmonic ordinal numbers of representative slot and pole number combinations are derived analytically with open-circuit and under load. Amplitudes of radial force waves are calculated by means of the finite element method and two-dimensional Fourier analysis. The obtained results confirm the analytical investigation. Determining factors on amplitudes are analyzed on a machine having 12 slots, 10 poles and a double-layer winding. Higher frequency harmonics can be significantly affected by pole and tooth shaping. With open-circuit, the calculations are validated by experimental results. ©2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.harmon
Keywords: Concentrated windings; External rotor; Finite element analysis; Ordinal numbers; Permanent magnet synchronous motor; Radial force waves; Resonant vibrations